Reckoning with identity: the changing dynamics of television representations in the American South - Scroggins, Emily, author; Diffrient, David Scott, advisor; Burgchardt, Carl, committee member; Gudmestad, Robert, committee member (Colorado State University. Libraries, 2022)
The American South is a continually understudied and misrepresented region of the United States. Televisual representations of the region typically rely on the Southern Imaginary, a collection of predetermined stereotypes and ideas about the South, to inform their depictions of Southerners and their identities. These representations tend to be one-dimensional and inauthentic to those who have and continued to live in the region. Recently, media depictions of the American South are attempting to challenge the Southern Imaginary and present a more nuanced and legitimate representation of Southerners. This project investigates how the nuanced representations of race, gender, and sexuality coupled with the settings of Hart of Dixie (CW, 2011-2015), One Mississippi (Amazon, 2015-2017), and Atlanta (FX, 2016-present) work to influence audiences' perceptions of the Southern region of the United States. Ultimately, I address the question: in what ways are modern television depictions of the South fighting against the Southern Imaginary and how does this influence the audiences' understanding of the South as both an actual regional space and a discursive construct? Investigation into the attempts to alter the Southern Imaginary can shed light on the falsities that television depictions of the region utilize to ensure that the South remains a social and political scapegoat for problems of the entire nation thus stagnating progress for all.
Keywords: gender; sexuality; American South; television; race